Genetic and physiological determinants of Streptomyces scabies pathogenicity - LERAT, SYLVAIN (Mol Plant Pathol, 2009)
Common scab is a severe disease worldwide affecting tap root crops and potato tubers. It is caused by soil‐borne filamentous bacteria belonging to the genus Streptomyces. Streptomycetes usually are saprophytic microorganisms, but a few species have acquired the ability to infect underground plant tissues. The predominant causal agent of potato scab worldwide is Streptomyces scabies. The production of phytotoxins called thaxtomins is essential for the virulence of common scab‐causing agents. The genes involved in the biosynthetic pathway of thaxtomins and other virulence genes are clustered on a large pathogenicity island. The pathogenicity island can be mobilized and transferred to nonpathogenic relatives, leading to the emergence of new pathogenic streptomycetes. In most pathogenic Streptomyces species, thaxtomin A is the predominant form found. The regulation of thaxtomin A synthesis is complex. Although the plant‐derived compound cellobiose is now recognized as the inducer of thaxtomin A synthesis at a genetic level, other molecules (including aromatic amino acids and some secondary metabolites) show inhibitory effects on the production of the toxin. This paper is an overview of common scab with a focus on S. scabies and its virulence mechanisms. Taxonomy: Streptomyces scabies (Thaxt.) Lambert and Loria; Kingdom Bacteria; Phylum Actinobacteria; Class Actinomycetes; Order Actinomycetales; Family Streptomycetaceae; genus Streptomyces; species scabies or scabiei. Host range: Streptomyces scabies (syn. S. scabiei) has a broad host range comprising tuber vegetables and most tap root crops. Streptomyces scabies causes common scab on potato (Solanum tuberosum), beet (Beta vulgaris), carrot (Daucus carota), parsnip (Pastinaca sativa), radish (Raphanus sativus), rutabaga (Brassica napobrassica) and turnip (Brassica rapa). Disease symptoms: Common scab symptoms appear as randomly distributed shallow, raised or deep‐pitted corky lesions. Their size and colour are quite variable, but lesions typically are brown with a diameter of a few millimetres. No above‐ground symptoms disclose the presence of the disease as aerial tissues of scab‐infected plants remain healthy. Streptomyces scabies also inhibits the growth of seedlings in monocot and dicot plants. Useful websites: http://www.sanger.ac.uk/Projects/S_scabies, http://www.potatodiseases.org/scab.html, http://www.uri.edu/ce/factsheets/sheets/potatoscab.html